The Colonization of the Future - Murphy, John W. (Sociologija. Mintis ir veiksmas, 2008)
Central to this paper is the idea that the world, including the future, is in the process of being colonized. In general, what this means is that persons do not have control of their experiences. In terms supplied by Marx, they are alienated and lost in a threatening world.To be post-colonial means that persons have gained the insight necessary to retrieve history. Ratherthan enslaved by history, and thus determined a priori by social conditions, they are able to create themselves and new institutional arrangements. They are not restricted by history, and thus unable to invent the future, but can begin to rethink radically about the nature of collective identity and social integration. Only in this manner can the remnants of colonization be abandoned.In order to counteract colonization, what is needed is more utopian thought. Contrary to what manycritics may believe, utopianism is neither irrational nor indicative of fantasy. Central to utopian thinking, instead, is a refusal to be entrapped in the traditional portrayal of social reality.
Keywords: colonization; history; rationalization; utopianism